The burden of headache disorders among medical students in Vietnam: estimates from a cross-sectional study with a health-care needs assessment - Dung Viet Nguyen; Hieu Trung Vo; Khoi Hong Vo; Lam Tung Duong; Lam Que La; An Bao Hoang; Phu Hong Vo; Thao Thu Tran; Binh Van Phan; Huong Thi Thu Pham; Hai-Anh Nguyen; Nga Thi Bui; et al. (The Journal of Headache and Pain)
Abstract Background In our previous study, we demonstrated that headaches are highly prevalent among medical students in Vietnam. In the present study, we provide estimates of the associated symptom burden and impaired participation, utilizing these estimates to assess headache-related healthcare needs within this population. Methods The study followed the standardized methodology established by the Global Campaign against Headache. Participants included medical students who were randomly selected from two medical universities in Vietnam. Data collection utilized the HARDSHIP questionnaire, which included diagnostic questions based on ICHD-3 criteria, measures of symptom burden, quality of life (QoL) assessments using the WHOQoL-8, evaluations of impaired participation through the HALT index, and questions about headache yesterday (HY). The definition of health care “need” was based on the likelihood of benefit from intervention, including all participants with probable medication-overuse headache (pMOH), other headaches occurring on ≥ 15 days/month (H15+), migraine on ≥ 3 days/month, or migraine or tension-type headache (TTH) meeting at least one of two criteria related to symptom burden and impaired participation. Results A total of 1,362 participants (57.3% female) were included, of whom 1,125 students (61.3% female) were diagnosed with a headache disorder, and 165 students (69.1% female) reported experiencing a HY. The mean frequency of any headache was 3.6 days per month, with an average duration of 5.3 h, and 58% of participants reported an intensity of moderate/severe. For all headache, the mean pTIS was 2.8%. The mean number of lost days over a period of 3 months was 4.3 for work/school tasks, 3.8 for household chore, and 1.7 for social or leisure activities. Among those reporting a HY, 35.8% were able to complete less than half of their expected activities, while 9.7% could complete none. QoL of students with any headache was significantly lower than that of students without headache. A mong students with headache, 43.8% fulfilled atleast one of our needs assessment criteria. Conclusions This first study on headache burden in Vietnam reveals substantial symptom burden alongside a correspondingly high level of impaired participation among medical students.